CHARACTER AND MORAL VALUE “IN THE SOUND OF MUSIC” BY ROBERT WISE - Aan Handayani; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2020)
The research aims to analyze the characters and moral values contained in the film "TheSound of Music" by Robert Wise. Based on the theories of character and moral values, there are four primary points to analyze: 1) There are three kinds of characters that appear in the characters in "The Sound of Music" by Robert Wise based on Russel, those are the Protagonist, the main protagonist played by Maria and the Von Trapp Family and the sisters in the monastery, the Antagonist, played by The Baroness and Herr Zeller, and Foil character played by Rolfe and Franz, 2) There are seven types of moral values that appear in "The Sound of Music" by Robert Wise based on Borba, they are respect, kindness, conscience, self-control, justice, empathy and tolerance.Keywords: content analysis; moral values; movie